A Hoard of Roman Republican and Norican coins from the vicinity of Kobarid - Kos, Peter; Žbona Trkman, Beatriče (Arheološki vestnik, 2009)
A hoard of Roman Republican silver and bronze coins as well as local small silver coins has been found by a prehistoric trail along the Soča River, connecting the hill-forts of Gradič near Kobarid and Tonovcov grad. It was deposited at the beginning of the second half of the 2ndcent. BC and reflects the everyday monetary circulation at that time, along with the chronological framework for the minting of the Norican small silver coins